(untitled) (The Journal of Building and Land Development, 2025)
Tanzania produces 2.33 million tons of rice annually, generating large quantities of rice husks, of which 20-25% are improperly managed, thus contributing to environmental degradation. This study investigated the use of rice husks ash as partial substitute for clay in the lightweight brick production, aiming to convert agricultural waste into value added construction materials. Bricks were fabricated using rice husk ash to clay ratios of 20:80 (LWB-A), 25:75 (LWB-B), 50:50 (LWB-C), and 80:20 (LWB-D) and then fired at different temperature (800°C, 900°C, and 1000°C). The bricks were evaluated for compressive strength, water absorption and density. Results indicated that rice husk ash contribute to reduced bulk density (down to 0.226 g/cm³), while maintaining structural performance when appropriately blended with clay. The optimal formulation (LWB-B), and fired at 1000°C achieved a compressive strength of 7.95N/mm², water absorption of 15% and density of 1606kg/m³, meeting standard requirement for lightweight construction bricks. These findings demonstrate the technical viability of rice husk ash as a sustainable additive in bricks manufacturing. Further research is recommended to optimize material behavior and assess environmental and economic implications for large-scale application.